2015
DOI: 10.3109/08820139.2014.1003651
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: The Relationship Between CTLA-4 +49 A/G Polymorphism and Primary Biliary Cirrhosis and Type I Autoimmune Hepatitis

Abstract: This meta-analysis concluded that the CTLA-4 G allele and the AG genotype were associated with an increased risk for PBC and AIH-1, respectively, suggesting the CTLA-4 +49 A/G polymorphism as a candidate of susceptibility locus to PBC and AIH-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…For patients in cases, the frequencies of allele and genotype in rs231775 and rs231725 were increased more significantly than those in controls. As to allele, the results of rs231775 were similar to the results of five published meta-analyses by Eskandari-Nasab et al [39], Huang et al [23], Miyake et al [24], Li et al [25], and Chen et al [14]. Li and Miyake indicated that the G allele might be connected with PBC as a risk factor.…”
Section: Discussionsupporting
confidence: 85%
“…For patients in cases, the frequencies of allele and genotype in rs231775 and rs231725 were increased more significantly than those in controls. As to allele, the results of rs231775 were similar to the results of five published meta-analyses by Eskandari-Nasab et al [39], Huang et al [23], Miyake et al [24], Li et al [25], and Chen et al [14]. Li and Miyake indicated that the G allele might be connected with PBC as a risk factor.…”
Section: Discussionsupporting
confidence: 85%
“…As an immunogenetic factor other than HLA, the cytotoxic T-lymphocyte antigen-4 (CTLA-4) +49 A/G polymorphism may be associated with a susceptibility to AIH 16. However, a recent genome-wide association study of genetic susceptibility to AIH showed a strong association only between the HLA locus and AIH, while dozens of weak susceptibility loci were determined 17.…”
Section: Immunogenetic Background Of Aihmentioning
confidence: 99%
“…The human leukocyte antigens (HLA) DRB1 gene is a well-characterized susceptibility gene and previous studies have identified DRB1*0301, DRB1*0401 associated with the genetic predisposition in Caucasian individuals and DRB1*0405 in Asian individuals[6, 7]. Genetic studies looking outside HLA genes have discovered the polymorphisms of cytotoxic T lymphocyte antigen–4 gene (CTLA-4), tumor necrosis factor–α gene (TNF-α) and Fas as potential non-HLA susceptibility gene to AIH-1[8, 9]. Recently, a genome-wide association study (GWAS) of Japanese AIH patients has identified at least 26 candidate AIH susceptibility or resistance regions other than HLA class II loci, while the GWAS of Dutch AIH patients has yielded 9 independent non-HLA susceptibility loci[10, 11].…”
Section: Introductionmentioning
confidence: 99%